2021
DOI: 10.1126/sciimmunol.abe6291
|View full text |Cite
|
Sign up to set email alerts
|

Single-cell analysis of human B cell maturation predicts how antibody class switching shapes selection dynamics

Abstract: Protective humoral memory forms in secondary lymphoid organs where B cells undergo affinity maturation and differentiation into memory or plasma cells. Here, we provide a comprehensive roadmap of human B cell maturation with single-cell transcriptomics matched with bulk and single-cell antibody repertoires to define gene expression, antibody repertoires, and clonal sharing of B cell states at single-cell resolution, including memory B cell heterogeneity that reflects diverse functional and signaling states. We… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

31
221
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 198 publications
(252 citation statements)
references
References 80 publications
31
221
0
Order By: Relevance
“…We also found a small and unexpected cluster of B cells expressing markers of type I interferon response genes such as IFI44L, XAF1, and MX1 (Fig1f-g) that are known to be up-regulated after early stages of vaccination (9). These annotations broadly agreed with recent single-cell studies of lymphocytes in pediatric tonsils and adult lymph node (10,11).…”
Section: Resultssupporting
confidence: 89%
See 3 more Smart Citations
“…We also found a small and unexpected cluster of B cells expressing markers of type I interferon response genes such as IFI44L, XAF1, and MX1 (Fig1f-g) that are known to be up-regulated after early stages of vaccination (9). These annotations broadly agreed with recent single-cell studies of lymphocytes in pediatric tonsils and adult lymph node (10,11).…”
Section: Resultssupporting
confidence: 89%
“…Other scRNA-seq analyses have recently demonstrated that tonsils are a transferable model tissue to study secondary lymphoid organs and adaptive immune responses more generally (10, 11, 16). In contrast to circulating or bone-marrow resident lymphocyte populations, immune cells within secondary lymphoid organs exist in a range of activation and maturation states, including GC-associated populations, that may reflect varied tissue niches, cell-cell communication and cytokine signaling.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This study resolved a critical question in the field placing CSR in the early events during GC initiation, and validated earlier evidence that CSR might occur prior to mature GCs (33,34). The transcriptional states associated with CSR have now been resolved at the single cell level, further accelerating our understanding of early events in the GC reaction (35).…”
Section: Class Switch Recombination Occurs During the Gc Initiation Phasesupporting
confidence: 76%